2022
DOI: 10.1002/cphc.202200035
|View full text |Cite
|
Sign up to set email alerts
|

Exploring AuRh Nanoalloys: A Computational Perspective on the Formation and Physical Properties

Abstract: We studied the formation of AuRh nanoalloys (between 20–150 atoms) in the gas phase by means of Molecular Dynamics (MD) calculations, exploring three possible formation processes: one‐by‐one growth, coalescence, and nanodroplets annealing. As a general trend, we recover a predominance of Rh@Au core‐shell ordering over other chemical configurations. We identify new structural motifs with enhanced thermal stabilities. The physical features of those selected systems were studied at the Density Functional Theory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
(133 reference statements)
1
5
0
Order By: Relevance
“…The first‐principles approaches are the only one capable of predicting and understanding the appearance of plasmon resonances in ultrasmall alloy NPs. Besides, the predominance of core‐shell ordering over other chemical configurations emerges in this size range at the boundary between molecular and solid‐state behaviour, which is evidenced by the models and must be considered for the interpretation of the resulting optical properties [131] …”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The first‐principles approaches are the only one capable of predicting and understanding the appearance of plasmon resonances in ultrasmall alloy NPs. Besides, the predominance of core‐shell ordering over other chemical configurations emerges in this size range at the boundary between molecular and solid‐state behaviour, which is evidenced by the models and must be considered for the interpretation of the resulting optical properties [131] …”
Section: Modellingmentioning
confidence: 99%
“…Besides, the predominance of core-shell ordering over other chemical configurations emerges in this size range at the boundary between molecular and solid-state behaviour, which is evidenced by the models and must be considered for the interpretation of the resulting optical properties. [131] Recently, TD-DFT and TD-DFT + TB (tight binding) were used to compute the absorption spectra of AuÀ Ag clusters in the 10-10 2 atoms range. [132,133] They evaluated how the scalar-relativistic (SR) and the spin-orbit (SO) contribution affect the optical properties and the transition from molecular-like to metal-like (plasmonic) optical excitations.…”
Section: First-principles Modelling Of the Optical Absorption Of Smal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Au L 3 -edge corresponded to the electronic transition from 2p 3/2 to the vacant 5d state, the decrease of the intensity of the white line indicated an increase of the electron density of Au 5d orbitals, indicating that alloying between Au and Rh induced electron transfer from Rh atoms to Au atoms of a larger ionization energy. 60 Furthermore, XANES spectra of the Rh K-edge (Fig. 5b) revealed that the absorption intensity of NPs at near 23 230 eV increased with an increase in the Rh fraction in comparison with Rh foil.…”
Section: Resultsmentioning
confidence: 94%
“…16 The prediction of the equilibrium morphology in metallic NPs has been performed by various computational approaches. [17][18][19][20][21][22][23][24] Such an example are Monte Carlo simulations based on semi-empirical potentials derived from the individual potentials calculated for each atom type by density functional theory. However, this approach is limited at a few thousand atoms and on a short timescale compared to most of the real world applications of nanoalloys.…”
Section: Introductionmentioning
confidence: 99%